Outpatient ESD for challenging colorectal lesions: Is it feasible and safe for western countries? - Pecere, Silvia; Barbaro, Federico; Petruzziello, Lucio; Papparella, Luigi Giovanni; Napoli, Marco; Boskoski, Ivo; Costamagna, Guido (Endoscopy International Open, 2021)
Background and study aims The need for hospital beds during the COVID-19 pandemic almost overwhelmed the health care systems all over the world. Therefore, elective non-life-saving procedures were postponed. We decided to perform all colorectal endoscopic mucosal dissections (ESDs) for challenging lesions as outpatient procedures, organizing an ad hoc path to management of any delayed post-procedural complications. The aim of the present study was to retrospectively evaluate the feasibility and safety of outpatient ESD for colorectal tumors. Patients and methods From March 2020 to May 2020, outpatient colorectal ESDs were performed for 15 challenging lesions. We retrospectively investigated feasibility and safety of the procedures, rates of en bloc resection, and complications rates. Results The mean age of the patients was 66.5 years and 40 % of the them were on antiplatelet/anticoagulation therapy. Median size of removed lesions was 45 mm (range 32–77) and 38 mm (range 24 to 55) Five patients (33 %) had rectal tumors extending to the dentate line and four (26.6 %) were recurrences on a scar of previous endoscopic or surgical local resections. All complications, such as bleeding or visible microperforation, were managed endoscopically and no delayed perforations occurred. One patient had fever (37.5 °C), while three patients complained of anal pain after ESD for a rectal tumor that extended to the dentate line (RTDL); all patients were managed conservatively. Conclusion Outpatient colorectal ESD is feasible and safe for challenging lesions. It reduces costs of hospitalization but direct access to the endoscopy service to manage potential post-ESD complications should always be guaranteed.